2021
DOI: 10.48550/arxiv.2104.02521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perturbations and the Future Conformal Boundary

A. N. Lasenby,
W. J. Handley,
D. J. Bartlett
et al.

Abstract: The concordance model of cosmology predicts a universe which finishes in a finite amount of conformal time at a future conformal boundary. We show that for particular cases we study, the background variables and perturbations may be analytically continued beyond this boundary and that the "end of the universe" is not necessarily the end of their physical development. Remarkably, these theoretical considerations of the end of the universe might have observable consequences today: perturbation modes consistent w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(34 citation statements)
references
References 26 publications
5
29
0
Order By: Relevance
“…Introducing a linearly quantized power spectrum with k0 = 3.225 × 10 −4 Mpc −1 and spacing ∆k = 2.257 × 10 −4 Mpc −1 provides a better fit to the Planck 2018 observations than the concordance baseline, with ∆χ 2 = −8.55. Extending the results of Lasenby et al [1], we show that the requirement for perturbations to remain finite beyond the future conformal boundary in a universe containing dark matter and a cosmological constant results in a linearly quantized primordial power spectrum. It is found that the infrared cutoffs for this future conformal boundary quantized cosmology do not provide cosmic microwave background power spectra compatible with observations, but future theories may predict more observationally consistent quantized spectra.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…Introducing a linearly quantized power spectrum with k0 = 3.225 × 10 −4 Mpc −1 and spacing ∆k = 2.257 × 10 −4 Mpc −1 provides a better fit to the Planck 2018 observations than the concordance baseline, with ∆χ 2 = −8.55. Extending the results of Lasenby et al [1], we show that the requirement for perturbations to remain finite beyond the future conformal boundary in a universe containing dark matter and a cosmological constant results in a linearly quantized primordial power spectrum. It is found that the infrared cutoffs for this future conformal boundary quantized cosmology do not provide cosmic microwave background power spectra compatible with observations, but future theories may predict more observationally consistent quantized spectra.…”
supporting
confidence: 83%
“…There has been much historical discussion of the significance of low-multipole features in the cosmic microwave background power spectrum [2][3][4], with many proposed primordial mechanisms to explain these features with varying degrees of naturalness [5]. In a recent paper, Lasenby et al [1] proposed a novel mechanism for setting initial conditions on cosmological perturbations derived from considerations of the future conformal boundary in radiation dominated universes. The key prediction of this theory is a quantization of wavevectors for the primordial power spectrum of curvature perturbations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…finding they are sinusoidal with a constant wavelength of 2πkt 3 . The FIC primordial power spectrum therefore has uniformly spaced peaks which suggests a similarity to the quantized primordial power spectra considered in [31,32]. The pseudo-quantized primordial power spectrum of FIC may therefore provide an improved fit to the Planck observations as was found by Bartlett et al [32] for a fully quantized spectra.…”
Section: B Frozen Initial Conditionssupporting
confidence: 60%